A Novel Technique in Treatment of Midcarpal Instability: Hammock Technique - Özçelik, İsmail B.; Elawadlly, Haitham S.; Kayık, Uğur; Ağırdıl, Yücel (Journal of Wrist Surgery, 2025)
Midcarpal instability (MCI) is a relatively uncommon yet disabling condition that manifests with wrist pain, weakness, and diminished grip strength. Diagnosis is primarily clinical, supported by dynamic imaging modalities such as video fluoroscopy and 4D CT. Initial management typically involves non-operative measures including patient education, activity modification, pain control, dynamic splinting, hand therapy, and proprioceptive training. Surgical intervention is considered in cases refractory to conservative treatment.To describe our novel “Hammock Technique” as a surgical method for the management of midcarpal instability (MCI). We outlines the detailed surgical steps of the procedure, defines its indications, and presents the standardized postoperative rehabilitation protocol. Furthermore, we highlight potential complications and discuss the technique’s role within the current spectrum of treatment options for MCI.The Hammock Technique was developed to address ligament dysfunction and hyperlaxity in both the dorsal and palmar regions of the wrist, as well as around the scaphoid. This technique employs the palmaris longus tendon, incorporated with the wrist capsule, to achieve a “triple effect”: (1) reinforcement of the dorsal ligaments, (2) hammock-like support for the proximal capitate and (3) stabilization of the scaphoid through fixation of its distal pole. It is particularly indicated for mild to moderate cases of midcarpal instability and can be effectively applied to both palmar and dorsal subtypes.Application of the Hammock Technique demonstrated improved midcarpal stability, restoration of functional wrist motion, and enhanced grip strength in patients with mild to moderate MCI. Early outcomes suggest reproducibility and safety, with a low complication rate.The Hammock Technique represents a simple, biologically sound, and effective surgical option for the treatment of mild to moderate MCI. It can be applied to both palmar and dorsal subtypes, offering satisfactory stability and functional outcomes while preserving native wrist kinematics.
Keywords: midcarpal instability; intrinsic; extrinsic; proprioception; videofluoroscopy; hammock technique; palmaris longus